Menakar Kesiapan Lembaga Perkreditan Desa (LPD) Jimbaran Dalam Merespon Kebijakan Relaksasi Kredit - A.A.N Oka Suryadinatha Gorda; Ni Kadek Mellynia Cahya Ningsih; I Made Mai Noval (Universitas Pendidikan Ganesha, 2023)
Abstract During the Covid-19 pandemic, there were many problems that occurred, one of which was credit problems. With this problem, the government takes steps to help the community, namely the government issued a credit relaxation policy. This credit relaxation is a loan of credit requirements, both financial and non-financial requirements to provide convenience to bank customers. The purpose of this study is to measure the readiness of the Jimbaran LPD in responding to credit relaxation policies. In this study using qualitative and quantitative types of data, using data collection techniques through the process of interviews, observations, and documentation. The results of this study are based on data analysis, it can be concluded that Jimbaran LPD has been able to apply this credit relaxation policy, LPD Jimbaran imposed a credit interest cut of 0.1%, providing an easing in credit payments which during the Pandemic Covid-19 Credit is allowed to only pay the interest interest only. Keywords : Credit issues, credit relaxation policies